Shifting to innovation putting the Philippine Microelectronics Industry at the forefront of development. - Tabangcura, M.
Throughout the world, the electronics industry has become a key factor in development. In 1998 alone, revenues from the industry reached (US)1,000 Billion and the number continues to grow at a dizzying pace. The semiconductor industry is expected to grow at a rapid rate over the next five years. Because of this, many industries have expressed interest in strengthening the microelectronics base. This goal makes necessary the establishment and forging of a link among the industry, the government, and the academe which is the key contributor to research and future advancements. Annual Semiconductors and Electronics Industry of the Philippines, Inc. (SEIPI) reports show a rapid increase in Philippine electronic equipment and component exports, starting from US 2.97B (28 percent of the total export figure)in 1992 to US 23.84B (67 percent of total Philippine Exports) in 1999. Export projections for the year 2004 amount to US 47.96B for the microelectronics industry, and the industry is expected to attract investments of US500 million annually. At present, the country is primarily engaged in semi-finished to finished electronic assembly, printed circuit board assembly, burn-in testing and other labor intensive manufacturing services. Truly, this is a far cry from the agricultural produce that the country was known for just over a decade ago a proof that the Philippines is capable of achieving every developing country's dream of becoming a key player in one of the largest and fastest growing industries throughout the world. However, for an industry that is expected to "propel the country's growth over the next decade", more should be done to ensure that the Philippines forges ahead to the forefront of technological development. Whereas the country's manpower and funding is currently being poured into component manufacturing and testing, steps However, for an industry that is expected to "propel the country's growth over the next decade", more should be done to ensure that the Philippines forges ahead to the forefront of technological development. Whereas the country's manpower and funding is currently being poured into component manufacturing and testing, steps need to be taken to involve the nation's resources in component and system design.